Effects and mechanisms of resistance training on corticospinal adaptation - Liang, Chengjun; Liu, Honglin (Frontiers in Physiology, 2025)
Resistance training has a wide range of applications in sports, national fitness, and sports rehabilitation. In the early stages of resistance training, muscle volume did not show significant changes, but strength increased significantly, mainly due to adaptive changes in the human nervous system. This article focuses on exploring the effects and mechanisms of resistance training on the human corticospinal central nervous system, aiming to provide a theoretical reference for the scientific design of resistance training programs in various fields. Resistance training can enhance corticospinal excitability, lower the threshold for active movement, and increase the motor-evoked potential with increasing resistance training intensity. Resistance training significantly reduced short interval cortical inhibition and shortened the duration of cortical silence. After resistance training, the active muscle recruitment curve area significantly increased. Resistance training reduces the degree of coactivation between the agonist and antagonist muscles, reduces the cortical inhibitory effect of the active muscle, and increases the cortical promoting effect. The mechanisms of excitatory changes in the central nervous system during resistance training mainly include corticospinal adaptation, reticulospinal tract adaptation, and spinal cord adaptation. These mechanisms are mainly achieved through increased synaptic connectivity of cortical spinal motor neurons or increased excitability of motor neurons, or through increased synaptic efficacy of projections from the reticulospinal to the spinal cord. The mechanism of cortical inhibition reduction mainly be achieved by sensory feedback reducing the excitability of cortical inhibition circuits or accompanying activation of cortical facilitation networks.